Separating fact from fiction: the truth about digital education - Saleh, Noor Shahariah; Abu Bakar, Ruhil Nadiah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Teaching used to be simple. There was once upon a time when students did not expect much from educators, and educators were free to decide how to handle the class based on the syllabus given. Following the pandemic, a transition is underway in teaching, particularly with the integration of digital lessons into the educational system as alternatives to conventional lessons. This has caused havoc not only among educators and students but also among parents. This is due to different sides of beliefs and misconceptions that were passed down. The misconceptions need to be highlighted and enlightened to enable society to understand and accept the future endeavour of digital learning in local education institutions.